Faktor Yang Memengaruhi Willingness to Pay Wisatawan Jabodetabek Dalam Rangka Mendukung Terciptanya Destinasi Pariwisata Yang Berkelanjutan - Nugraheni, Putri; Lemy, Diena Mutiara (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2023)
This research aims to determine the factors that influence the Willingness to pay of Jabodetabek Tourists in order to support the creation of sustainable tourism destinations. The method used in this research is descriptive quantitative. The sampling technique in this study was a non-probability sampling technique, using purposive sampling as a sub-technique, with a total of 100 respondents. The data collection technique in this study was by distributing questionnaires and processing them using multiple linear regression analysis methods. Meanwhile, the independent variables in this study are education level, recreation costs, income, frequency of visits and alternative locations, while the dependent variable is tourists’ willingness to pay. The results of this study indicate that the Education variable has a significant effect on tourists’ willingness to pay, because the higher the level of education, the easier it is for them to receive information regarding the importance of supporting the application of sustainable concepts to a tourism destination. In addition, the variable income in this study also has a significant effect on tourists’ willingness to pay, because the higher the income a person has, the greater the expenditure that can be set aside to support the creation of sustainable tourism destinations. Keywords: Education, Income, Tourists’ Willingness to pay